Case Report: A 42-year-old male with IABP developing multiple organ embolism and intestinal necrosis - Yang, Wanying; Lu, Jing; Du, Ting; Sha, Lulin; Wang, Wei; Wang, Xin; Gong, Qian (Frontiers in Cardiovascular Medicine, 2024)
We report a 42-year-old male patient who was diagnosed with acute myocardial infarction (AMI), and subsequently underwent percutaneous coronary intervention (PCI) for revascularization. The patient was transferred to the cardiac intensive care unit for intra-aortic balloon pump (IABP) due to frequent malignant arrhythmia after PCI. Then the patient experienced the most severe complications of IABP, including multiple organ embolism and intestinal necrosis. This report highlights the rare serious complications of IABP and the challenges encountered in handling this complex case.